Unraveling the influence of task designs and intrinsic motivation in effort-based decision-making. - Randez, Alyssa; Hélie, Sébastien (Memory & Cognition, 2026)
Cognitive effort-based decision-making typically focuses on how much effort a person chooses to invest in a given action. Past experiments follow the assumption that monetary means and cognitive demands influence effort investment. However, motivation can influence behaviors beyond these factors, leaving open the question as to how individual tasks can motivate effort. Using two experiments, this study investigated how different elements of task designs can contribute to preferences that are related to the costs of performing an action and the rewards of monetary incentives. The results of this study suggest that preferences for an option can be influenced by various task-related factors such as the cognitive components required to complete a task (e.g., motor- or memory-related), how demanding the options are relative to each other (as determined by the number of elements to be manipulated in the task), and how much reward is available after task completion. In some cases, task designs could explain decision-making tendencies better than monetary reward or demand levels. These findings have significant implications for understanding how intrinsic motivation affects preferences based on the requirements of a task that can be unrelated to ability.